Upaya Meningkatakan Hasil Belajar Tematik Integratif Melalui Model Problem Based Learning - Budiarti, Erni; Murtafiah, Wasilatul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2023)
Implementation of thematic learning that is carried out online is centered on the teacher so that it makes students not active when participating in lessons. The purpose of this study was to find out whether there was an increase in the learning outcomes of third grade elementary school students through Problem Based Learning (PBL). This type of research is classroom action research (CAR). The PTK model used is the spiral from C. Kemmis and Mc Taggart. The research procedure uses at least 2 cycles with a note that if each cycle shows an increase in learning outcomes, each cycle consists of planning, implementing actions and observing, and reflecting. Data collection techniques using test techniques. The research instrument is in the form of item questions. The results of the research show that the Problem Based Learning learning model has an effect on the learning outcomes of third grade elementary school students through PBL. It can be concluded that the PBL learning model can improve student learning outcomes. The implications of this research have an impact on an active and fun learning atmosphere so that it can improve student learning outcomes.